2011
DOI: 10.1103/physrevx.1.011008
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Conversation Partners

Abstract: Recent developments in sensing technologies have enabled us to examine the nature of human social behavior in greater detail. By applying an information-theoretic method to the spatiotemporal data of cellphone locations, [C. Song et al., Science 327, 1018(2010] found that human mobility patterns are remarkably predictable. Inspired by their work, we address a similar predictability question in a different kind of human social activity: conversation events. The predictability in the sequence of one's conversati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 49 publications
2
101
0
Order By: Relevance
“…Recent work has indicated that a first-order Markov model may fail to adequately predict real dynamics 15,20,23,26 . That is, real dynamics often have at least one-step memory, which conventional network analysis cannot capture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has indicated that a first-order Markov model may fail to adequately predict real dynamics 15,20,23,26 . That is, real dynamics often have at least one-step memory, which conventional network analysis cannot capture.…”
Section: Discussionmentioning
confidence: 99%
“…Shannon 10 introduced higher-order memory models in 1948, and there is a substantial body of work on analysing memory effects in, for example, time-series analysis for forecasting financial markets 11 , correlated random walks for predicting animal movements 12 and exponential random graph models for capturing social networks 13 . Moreover, there is recent evidence that memory is necessary for accurately predicting web traffic 14,15 , for improving search and navigation in information networks [16][17][18] and for capturing important phenomena in the spread of information [19][20][21][22][23] and epidemics [24][25][26][27][28][29] . Nevertheless, little is known about memory effects on community detection, ranking and spreading analysis, three principal methods in network science.…”
mentioning
confidence: 99%
“…Because the human body acts as a shield for the proximity-sensing RF signals, such sensors only record contacts when the individuals are facing each other, and thus a contact can also be considered as indicative of communication between the individuals [24,64,121,141]. Recording of face-to-face communication events has also been realized with infrared sensor devices [145]. Another type of largescale proximity data comes from hospitals where contacts between two patients that have been admitted to the same ward at the same time are recorded, sometimes including the medical staff [99,154].…”
Section: Physical Proximitymentioning
confidence: 99%
“…The standard approach of modeling dynamical processes on networks with first-order flows oversimplifies the real dynamics and sets a limit of what can actually be detected in the system (Figure 1). Capturing critical phenomena in the dynamics and function of complex systems therefore often requires models of higher-order network flows [5][6][7][23][24][25][26][27][28].…”
Section: First-order Network Flowsmentioning
confidence: 99%